2007
DOI: 10.1097/wnr.0b013e32801421ce
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Smoothened at hippocampal mossy fiber synapses

Abstract: The seven-transmembrane receptor Smoothened is essential for hedgehog signal transduction. In adulthood, the highest density of Smoothened mRNA is found in the granule cell layer of the dentate gyrus. There, Smoothened expression is regulated by the synaptic activity involving the glutamatergic transmission. The precise localization of Smoothened proteins, however, has not yet been reported. Here, we describe Smoothened protein distribution in the hippocampal mossy fibers using specific Smoothened antibodies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Since there is no significant increase before cilia formation, Kif3a or Ift88 likely modulates this pathway through its ciliary function rather than both ciliary and non-ciliary functions, as previously reported 19 . Furthermore, the lack of Smoothened expression in the granule cell and molecular layers in the dentate gyrus makes it unlikely that hedgehog signaling is involved in dendritic refinement during this period 4344 . With regard to the second question, the data (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Since there is no significant increase before cilia formation, Kif3a or Ift88 likely modulates this pathway through its ciliary function rather than both ciliary and non-ciliary functions, as previously reported 19 . Furthermore, the lack of Smoothened expression in the granule cell and molecular layers in the dentate gyrus makes it unlikely that hedgehog signaling is involved in dendritic refinement during this period 4344 . With regard to the second question, the data (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…One previous study reported Smo’s “exclusively” presynaptic expression in the hippocampal mossy terminal (Masdeu et al, 2007; reviewed in Traiffort et al, 2010). However, we find that Ptch and Smo are present predominately in the spines and dendrites of hippocampal neurons; this pattern is seen in vitro of cultured neurons and in vivo of different types of synapses in several regions of the hippocampus (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies. A previously described polyclonal rabbit antiserum against rat Smo was used (Masdeu et al, 2007). The mouse antiacetylated tubulin antibody and the mouse monoclonal anti-c-myc antibody were obtained from Sigma; the goat anti-mouse Alexa Fluor 546 antibody was obtained from Invitrogen (Leiden, The Nederlands); and the goat anti-rabbit fluorescein isothiocyanate antibody from Millipore Bioscience Research Reagents (Temecula, CA).…”
Section: Methodsmentioning
confidence: 99%